Stabilin-1 is expressed in human breast cancer and supports tumor growth in mammary adenocarcinoma mouse model - Riabov, Vladimir; Yin, Shuiping; Schledzewski, Kai; Sticht, Carsten; Schmuttermaier, Christina; Schönhaber, Hiltrud; Weiß, Christel; Simon-Keller, Katja; Berlit, Sebastian; Marx, Alexander; Goerdt, Sergij; Kzhyshkowska, Julia (OncoTarget, 2016)
Stabilin-1 is a multifunctional scavenger receptor expressed on alternatively-activated macrophages. Stabilin-1 mediates phagocytosis of “unwanted-self” components, intracellular sorting, and endocytic clearance of extracellular ligands including SPARC that modulates breast cancer growth. The expression of stabilin-1 was found on tumor-associated macrophages (TAM) in mouse and human cancers including melanoma, lymphoma, glioblastoma, and pancreatic insulinoma. Despite its tumor-promoting role in mouse models of melanoma and lymphoma the expression and functional role of stabilin-1 in breast cancer was unknown. Here, we demonstrate that stabilin-1 is expressed on TAM in human breast cancer, and its expression is most pronounced on stage I disease. Using stabilin-1 knockout (ko) mice we show that stabilin-1 facilitates growth of mouse TS/A mammary adenocarcinoma. Endocytosis assay on stabilin-1 ko TAM demonstrated impaired clearance of stabilin-1 ligands including SPARC that was capable of inducing cell death in TS/A cells. Affymetrix microarray analysis on purified TAM and reporter assays in stabilin-1 expressing cell lines demonstrated no influence of stabilin-1 expression on intracellular signalling. Our results suggest stabilin-1 mediated silent clearance of extracellular tumor growth-inhibiting factors (e.g. SPARC) as a mechanism of stabilin-1 induced tumor growth. Silent clearance function of stabilin-1 makes it an attractive candidate for delivery of immunomodulatory anti-cancer therapeutic drugs to TAM.
Gesehen am 14.05.2019